2019
DOI: 10.1016/j.physd.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

On the symmetry properties of a random passive scalar with and without boundaries, and their connection between hot and cold states

Abstract: We consider the evolution of a decaying passive scalar in the presence of a gaussian white noise fluctuating linear shear flow known as the Majda Model. We focus on deterministic initial data and establish the short, intermediate, and long time symmetry properties of the evolving point wise probability measure (PDF) for the random passive scalar. We identify, for the cases of both point source and line source initial data, regions in the x-y plane outside of which the PDF skewness is sign definite for all time… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 25 publications
5
22
0
Order By: Relevance
“…Here, the role of boundaries in setting the long time limiting skewness of the PDF is established rigorously for the above class using the long time asymptotic expansion of the N -point correlator of the random field obtained from the ground state eigenvalue perturbation approach proposed in [6]. Our analytical result verifies the conclusion for the linear shear flow obtained from numerical simulations in [11]. Moreover, we demonstrate that the limiting distribution is negatively skewed for any shear flow at sufficiently low Péclet number.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…Here, the role of boundaries in setting the long time limiting skewness of the PDF is established rigorously for the above class using the long time asymptotic expansion of the N -point correlator of the random field obtained from the ground state eigenvalue perturbation approach proposed in [6]. Our analytical result verifies the conclusion for the linear shear flow obtained from numerical simulations in [11]. Moreover, we demonstrate that the limiting distribution is negatively skewed for any shear flow at sufficiently low Péclet number.…”
supporting
confidence: 68%
“…We focus on a broad class of nonlinear shear flows multiplied by a stationary, Ornstein-Uhlenbeck (OU) time varying process, including some of their limiting cases, such as Gaussian white noise or plug flows. For the former case with linear shear, recent studies [11] numerically demonstrated that the decaying passive scalar's long time limiting probability distribution function (PDF) could be negatively skewed in the presence of impermeable channel boundaries, in contrast to rigorous results in free space which established the limiting PDF is positively skewed [26].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…For periodic boundary conditions, Bronski and McLaughlin [7] carried out a second order perturbation expansion for the ground state of periodic Schrödinger equations to analyze the inherited probability measure for a passive scalar field advected by periodic shear flows with multiplicative white noise. In [11,10], equation ( 3) was studied with a stationary OU process, where a dramatically different long time state resulting from the existence of the impermeable boundaries was found. In particular, the PDF of the scalar in the channel case has negative skewness for sufficiently small Péclet number, in stark contrast to free space, where the limiting skewness is strictly positive for all Péclet number.…”
Section: Setup and Background Of The Majda Modelmentioning
confidence: 99%
“…This established that for integrable random initial data the PDF would 'Gaussianize' at long times, whereas short ranged, random wave initial data would produce divergent flatness factors in the same limit as finite times. Recently, the role of impermeable boundaries in the Majda model has been explored in a parallel-plate channel with deterministic initial conditions [11,10]. Those works demonstrate that the sign of long time PDF skewness could be controlled by Péclet numbers and the correlation time of the velocity field, in strong contrast with the free space result, where the long time PDF skewnness is strictly positive.…”
Section: Introductionmentioning
confidence: 99%